The Students Motivation Toward the Use of Informatics Technology In Teaching English at MA Ma’arif Roudlotut Tholibin - Retno Wulandari; Suhono Suhono; Umar Al faruq A Hasyim; Mukminatus Zuhriyah; Yeasy Agustina Sari (CV. Creative Tugu Pena, 2025)
This study is motivated by the continuous changes in people’s lives resulting from advances in science and technology, particularly in education. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Information was obtained from the head of the madrasah, the chairman of the madrasah committee, teachers, and students. Data were analyzed using a descriptive narrative technique through the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured through triangulation of respondents, methods, and time. The findings reveal that the use of information technology, specifically the WhatsApp application, in the learning process at MA Ma'arif Roudlotuth Tholibin, serves not only as a medium, source, and tool for evaluation but also as a stimulus for student engagement. Students reported feeling less bored, more motivated, and more actively involved in learning. The use of WhatsApp as a learning medium helps overcome students’ limited experiences, fosters interaction with their environment, ensures uniformity of understanding, and supports the development of appropriate basic concepts. Furthermore, it enhances students’ interests, regulates learning pace, and provides a comprehensive learning experience from concrete to abstract concepts. Contribution: This study contributes to the field of educational technology by demonstrating how the integration of a widely accessible communication tool—WhatsApp—can effectively enhance student motivation, engagement, and learning outcomes in a madrasah context. It highlights the potential of low-cost, familiar platforms to bridge technological gaps in education and to create more dynamic and interactive learning environments.